ANALISIS FLUKTUASI KURS, CADANGAN DEVISA DAN PRODUK DOMESTIK BRUTO (PDB) TERHADAP FLUKTUASI EKSPOR UBI KAYU INDONESIA - Hikmatul Fadila; Asnawi Asnawi (LPPM Universitas Malikussaleh - Indonesia, 2024)
This study aims to determine exchange rate fluctuations, foreign exchange reserves, and Gross Domestic Product on fluctuations in cassava exports in Indonesia. The data used in this study are secondary in the form of a time series from 1986 to 2021, obtained from the World Bank and the Food and Agriculture Organization (FAO). The data analysis method in this study is Vector Auto Regression (VAR) using Eviews 10. The results of this study show that exchange rate fluctuations have a negative and insignificant effect on fluctuations in cassava exports in Indonesia. The fluctuations of foreign exchange reserves have a negative and significant impact on fluctuations in cassava exports in Indonesia. The fluctuations in Gross Domestic Product have a positive and insignificant effect on fluctuations in cassava exports in Indonesia.